Depression, Anxiety and Stress among Students amidst COVID-19 Pandemic: A Cross-Sectional Study in Philippines - Joel Rey U. Acob; Hidayat Arifin; Yulis Setiya Dewi (Faculty of Nursing Universitas Padjadjaran, 2021)
Background: COVID-19 considered as a global health crisis poses mental health problems among individual and specifics to students. Purpose: This study aimed to determine the depression, anxiety, and stress levels among students amidst COVID-19 pandemic in Philippines. Methods: A cross-sectional study was undertaken in Region 8, Eastern Visayas Philippines. A total of 311 tertiary respondents randomly selected both private and government owned higher education institutions. The data compilation was done using online questionnaires through Google Forms with validated version of the Stress, Anxiety and Depression Scales 21 (DASS21) is used to calculate students’ level of stress, anxiety and, depression with their socio-demographic features. Results: We revealed that depression, anxiety and stress are instituted in 18.6 %, 35.1 % and 2.85% of students, respectively, amidst the COVID – 19 pandemics. The symptoms of disorders were moderate to extremely severe in 6.1%, 23.5%, and 0.6% of the study sample, respectively. Age, gender, marital status and family history of illness are significantly different with age group 20 and below, females, singles, and families with no history of illness displaying high level of anxiety. Results also established an association between anxiety and family’s monthly income and history of illness. The higher the monthly income and no presence of illness of families, the more anxious the person. Conclusion: Finally, the variables used, explained only 1.5% depression, 3.4% anxiety and 1.4% stress in this time of COVID-19 outbreak. It is therefore recommended to essentially develop community-based mental health program for preventive purposes.